2014
DOI: 10.1021/nn406184r
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Induced by Zinc Oxide Nanoparticles Is an Earlier Biomarker for Nanotoxicological Evaluation

Abstract: Zinc oxide nanoparticles (ZnO NPs) have been widely used in cosmetics and sunscreens, advanced textiles, self-charging and electronic devices; the potential for human exposure and the health impact at each stage of their manufacture and use are attracting great concerns. In addition to pulmonary damage, nanoparticle exposure is also strongly correlated with the increase in incidences of cardiovascular diseases; however, their toxic potential remains largely unclear. Herein, we investigated the cellular respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
162
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(174 citation statements)
references
References 56 publications
6
162
3
3
Order By: Relevance
“…wed in Djur n D (Zhang et al 2012, Chen et al 2014, Yu, Chang, et al 2015. Our data show that the internalization of titanium (TiO 2 NPs), besides increasing the cell calcium content, does also induce the expression of CHOP (ATF4 pathway) and activates (i) the ER stress in HUVEC cells and (ii) differentiation in keratinocytes.…”
Section: Previous Studie Previous Stumentioning
confidence: 79%
See 1 more Smart Citation
“…wed in Djur n D (Zhang et al 2012, Chen et al 2014, Yu, Chang, et al 2015. Our data show that the internalization of titanium (TiO 2 NPs), besides increasing the cell calcium content, does also induce the expression of CHOP (ATF4 pathway) and activates (i) the ER stress in HUVEC cells and (ii) differentiation in keratinocytes.…”
Section: Previous Studie Previous Stumentioning
confidence: 79%
“…Recent studies report the endoplasmic reticulum stress (ER stress) as a common response in NPs related toxicity with studies on TiO 2 NPs (Zhang et al 2012, Chen et al 2014, Yu, Chang, et al 2015. The endoplasmic reticulum (ER) is an important organelle, which plays a role in folding and assembling of cellular proteins, in synthesis of lipids and sterols, and in regulating the balance of the intracellular calcium homeostasis, processes which are all dependent on the ER internal homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have previously shown induced endoplasmic reticulum (ER) stress in different cell types after treatment with silverdoped silica NPs, 40 silver NPs 41,42 or polystyrene nanospheres. 43 Chen et al showed that zinc oxide NPs triggered ER stress in HUVEC 44 and gold NPs were shown to induce stress signaling in K562 cells. 45 However, previous studies show that AuNPs of three different sizes and four detection of ER stress markers, which constitute components of the Unfolded Protein Response (UPR).…”
Section: Resultsmentioning
confidence: 99%
“…The airborne particles can be classified as ambient airborne particulate material (PM) which usually is categorized into coarse, fine, and ultrafine particles with aerodynamic diameters between 2.5 and 10 µm, < 2.5 µm (PM 2.5 ), and < 0.1 µm (PM 0.1 ), respectively (Hinds, 1999). It had been found that particles at the nanoscale level pose more adverse health effects than larger particles with the same materials (Nalwa and Zhao, 2007;Qu et al, 2011;Chen and Chen, 2012;Gorbunov et al, 2013;Chen et al, 2014). Understanding the health risks of aerosol particles under different environmental conditions, is of major necessity for improving exposure estimates, to develop efficient control strategies, to reduce human exposure and adverse health risks.…”
Section: Introductionmentioning
confidence: 99%